Desenvolvimento local e nível de organização social: estudo da disparidade entre dois municípios da região de Toledo PR - Barbosa, Adalberto Telesca (2012)
The administrative region of Toledo, located in the West of Paraná and consisted of twenty municipalities, as a whole, it is a thriving region, having in agribusiness the mainstay of its economy. However, when the development is analyzed with its municipalities in individualized ways, the local disparities are clear. There are many factors that can account for these local inequalities, among them we mention aspects linked to the colonization process, aspects linked to the soil productive capacity, land distribution, among others. In this study, we aim to analyze the organization of the local societies from their associative entity, making the comparison between two municipalities of the region; Maripá and São Pedro do Iguaçu, which, in spite of the similarity in territorial aspects, size of population and equidistance to the regional pole municipality, present high discrepancy when their development level is confronted. The capital stock of both municipalities showed important differences and that can explain the difference in local development level. The social organizations existing in the municipality with higher level of local development exist in greater quantity and have greater diversity in their object, making a network of associative entities which join economic-productive, social, cultural, recreational and religious interests. These entities are in service of the civil society promoting the union of interests which erupt into the productivity or aspects related to the marketing, in addition to promoting their associates well-being and also used by the local public authorities in accomplishment of activities of the population common interest. In the municipality with lower development, the local entities are in smaller numbers and those ones in which their object is related to religious and recreational ties predominate. However, in this municipality, as well, the local public authorities make use of the social organization as a way of implementing actions of public harmony and also promoting services of assistance issue, education and accomplishment to public policy requirements of state and federal scope.